2012
DOI: 10.3141/2280-09
|View full text |Cite
|
Sign up to set email alerts
|

Braking News

Abstract: Word count: 5,495 (text) + 8 × 250 (figures and tables) = 7,495 TRB 2012 Annual Meeting Paper revised from original submittal. ABSTRACTThis study focuses on the linkage between crash severity and crash avoidance maneuvers. Various emergency lateral and speed control maneuvers are considered in response to different critical events that made the crash imminent. Partial proportional odds models are estimated to accommodate the ordered-response nature of severity while allowing for changes in effects across sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This study found that most severe animal-vehicle crashes involved large wild animals, such as a deer. Kaplan & Prato (2012) noted that the "majority of drivers fail to take action when [faced with critical events]," possibly due to objective infrastructural, behavioral, or psychological constraints that result in delayed recognition of and reaction to the critical event. This was partly observed in our study as five of the 16 participants experienced complete stops or collisions with the deer obstacle, though instructed not to.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that most severe animal-vehicle crashes involved large wild animals, such as a deer. Kaplan & Prato (2012) noted that the "majority of drivers fail to take action when [faced with critical events]," possibly due to objective infrastructural, behavioral, or psychological constraints that result in delayed recognition of and reaction to the critical event. This was partly observed in our study as five of the 16 participants experienced complete stops or collisions with the deer obstacle, though instructed not to.…”
Section: Discussionmentioning
confidence: 99%